Respuesta :

Answer:

[tex]b_2 = \frac{2A}{h} -b_1[/tex]

Step-by-step explanation:

Given

[tex]A = \frac{1}{2}h(b_1 + b_2)[/tex]

Required

Select equivalent expressions

Multiply through by 2

[tex]2*A = 2*\frac{1}{2}h(b_1 + b_2)[/tex]

[tex]2*A = h(b_1 + b_2)[/tex]

[tex]2A = h(b_1 + b_2)[/tex]

Divide through by h

[tex]\frac{2A}{h} = \frac{h(b_1 + b_2)}{h}[/tex]

[tex]\frac{2A}{h} = b_1 + b_2[/tex]

Subtract b1 from both sides

[tex]\frac{2A}{h} -b_1= -b_1 + b_1 + b_2[/tex]

[tex]\frac{2A}{h} -b_1= b_2[/tex]

[tex]b_2 = \frac{2A}{h} -b_1[/tex]

From the list of options, there is only one answer

ACCESS MORE